Ansiedade, estresse e depressão em estagiários de psicologia do Triângulo Mineiro/Alto Paranaíba - Oliveira, Nadyara Regina de (2019)
In the last decade, several studies have focused on the mental health of university students. Conditions such as depression, anxiety and stress are present in university population in general, and this is not different among Psychology students. The internships in this area occur at the end of graduation. It is a delicate phase and not well enough investigated. Thus, the purpose of this study is to describe the sociodemographic profile of Psychology interns, their life habits, experience and academic satisfaction and the prevalence rates of depression, anxiety and stress, in Triângulo Mineiro. Also, the understanding of the relation between those conditions and habits and satisfaction of the students are analyzed. A questionnaire of socioeconomic data, life and academic habits were used to achieve that purpose, as well as the Depression Anxiety and Stress Scale (DASS-21) and Scale of Satisfaction with Academic Experiences (ESVA). Data collection was performed through SurveyMonkey platform. The interns were between 20 and 53 years old, from public (45.3%) and private institutions (54.7%), mostly women (89.8%) and more than half (60.2%) in the last year of the course. The results indicated that 63% of them suffers from depression, 66.9% from stress, 53.5% has anxiety and 3.9% low student satisfaction. Women had higher rates of anxiety. Having a previous psychiatric diagnosis had effect on the levels of stress, anxiety and depression. Dissatisfaction with the choice of the course was related to higher rates of anxiety and stress. The worst mental health evaluation was related to anxiety, depression and stress. Lower rates of student satisfaction were related to higher rates of depression. The interns presented high indexes of the pathologies evaluated in this study, indicating the need for immediate investment in prevention programs and promotion of mental health to the said population.